Tratamento de esgoto sanitário utilizando reatores anaeróbios operados em bateladas sequenciais (escala piloto) - Sarti, Arnaldo; Sakamoto, Isabel Kimiko; Varesche, Maria Bernadete Amâncio [UNESP]; Zaiat, Marcelo; Foresti, Eugenio (FapUNIFESP (SciELO), 2006)
The performances of two anaerobic sequencing batch reactors (1.2 m 3) containing biomass immobilized in inert support and as granular sludge in the treatment of domestic sewage from the Campus of São Carlos-University of São Paulo were evaluated. The experimental phase lasted seventy days. During this period, the reactors presented quite similar performances in respect to COD and total suspended solids removal, achieving average efficiencies of approximately 60% and 75%, respectively. The analysis using molecular biology techniques on biomass samples taken at 35 th and 70 th showed differences in the bacterial community in the reactors indicating that the type of biomass immobilization selected the populations differently. A higher similarity was found for the Archaea domain probably because these microorganisms utilize specific substrates formed at the end of the anaerobic process.
Domestic sewage treatment in pilot-scale anaerobic sequencing batch reactors
Keywords: Anaerobic treatment; Batch reactor; Domestic sewage; PCR/DGGE; Archaea; Bacteria (microorganisms)